Effect of hemodiafiltration with endogenous reinfusion on overt idiopathic chronic inflammation in maintenance hemodialysis patients: A multicenter longitudinal study. Issue 4 (28th May 2014) - Borrelli, Silvio; Minutolo, Roberto; De Nicola, Luca; De Simone, Emanuele; De Simone, Walter; Zito, Bruno; Guastaferro, Pasquale; Nigro, Filippo; Iulianiello, Giuseppe; Credendino, Olga; Bassi, Antonio; Leone, Luigi; et al.
Abstract Chronic inflammation is widely diffuse in maintenance hemodialysis (MHD) patients and is associated with poor survival. Hemodiafiltration with endogenous reinfusion (HFR) is a dialysis technique, highly biocompatible, able to adsorb proinflammatory cytokines and to decrease amino acids and antioxidants loss. These features could be helpful in MHD patients affected by idiopathic chronic inflammation, but this issue remains to be elucidated. We performed a multicenter longitudinal study to assess the effect of the switching from bicarbonate HD to HFR in patients with serum C‐reactive Protein (CRP) > 5 mg/L coupled with albumin <4.0 g/dL in the last 6 months. We enrolled 24/176 (14%) patients, of which 20 patients were assessed at 4 months and 18 completed the study. We excluded 11 patients with evident causes of inflammation. At baseline, serum levels of CRP (18.7[7.0–39.4] mg/L) and albumin (3.5[3.3–3.7] g/dL) were significantly correlated (r = −0.49; P = 0.028). The effect on CRP and albumin was almost evident in the first 4 months and remained stable until to eighth month. A strict correlation (R = −0.49; 0.040) between percentage change of CRP (−35%) and albumin (+14%) after 8 months of HFR. These effects were associated with the reduction of IL‐6, IL‐1β, and TNF‐α and the increment of pre‐albumin and leptin, whereas the serum levels of Branched Chain Amino Acid (BCAA) remained unchanged. In MHD patients affected by idiopathic chronic inflammation the switching from BHD to HFR is associated with improvement of inflammation. Whether these favorable effects may modify the outcomes of these high‐risk patients needs to be confirmed by studies ad hoc.